2022
DOI: 10.3389/fcell.2022.858272
|View full text |Cite
|
Sign up to set email alerts
|

dmrt2 and myf5 Link Early Somitogenesis to Left-Right Axis Determination in Xenopus laevis

Abstract: The vertebrate left-right axis is specified during neurulation by events occurring in a transient ciliated epithelium termed left-right organizer (LRO), which is made up of two distinct cell types. In the axial midline, central LRO (cLRO) cells project motile monocilia and generate a leftward fluid flow, which represents the mechanism of symmetry breakage. This directional fluid flow is perceived by laterally positioned sensory LRO (sLRO) cells, which harbor non-motile cilia. In sLRO cells on the left side, fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Therefore, we analyzed the somitogenic factor myf5 during gastrulation, which showed strong reductions under these conditions, indicating a high sensitivity of the paraxial tissues to a loss of Rab7 (Figures 2H-J). This strong inhibition of myf5, which has been implicated in LR symmetry breakage very recently (Tingler et al, 2022), suggested a potential impact on LRO sensor specification as well. Thus we wondered whether sLRO cells were specified correctly, i.e., expressed characteristic marker genes (Figure 2A).…”
Section: Lack Of Lr Organizer Sensor Specification Upon Rab7 Knockdownmentioning
confidence: 78%
See 1 more Smart Citation
“…Therefore, we analyzed the somitogenic factor myf5 during gastrulation, which showed strong reductions under these conditions, indicating a high sensitivity of the paraxial tissues to a loss of Rab7 (Figures 2H-J). This strong inhibition of myf5, which has been implicated in LR symmetry breakage very recently (Tingler et al, 2022), suggested a potential impact on LRO sensor specification as well. Thus we wondered whether sLRO cells were specified correctly, i.e., expressed characteristic marker genes (Figure 2A).…”
Section: Lack Of Lr Organizer Sensor Specification Upon Rab7 Knockdownmentioning
confidence: 78%
“…This correlates with the initial observation of Amaya and colleagues, who described exactly this paraxial sensitivity when using a dn-fgfr1 construct ( Amaya et al, 1993 ). Importantly, very recently Myf5 has been demonstrated to be required for LRO sensor formation in Xenopus , directly linking somitogenesis to LR asymmetry ( Tingler et al, 2022 ). Thus, inhibition of myf5 is sufficient to explain the LR defects obtained by loss of Rab7.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we designed genetic interaction studies to explore the relationship between esrrγa and ppargc1a . Suboptimal morpholinos (SOMOs) have been a consistent and well-established strategy to test whether multiple genes operate synergistically in a pathway in multiple species, including zebrafish and Xenopus laevis ( Chambers et al, 2020b ; Choi et al, 2015 ; DiBella et al, 2009 ; Epting et al, 2022 ; Fowler et al, 2021 ; Janssens et al, 2013 ; Kallakuri et al, 2015 ; Lefkopoulos et al, 2020 ; Lu et al, 2021 ; Maerker et al, 2021 ; Tingler et al, 2022 ; Wagle et al, 2011 ). Therefore, we injected SOMO doses of both esrrγa and ppargc1a , based on previously published doses ( Chambers et al, 2018 , 2020b ).…”
Section: Resultsmentioning
confidence: 99%